AWARENESS OF TUBERCULOSIS AMONG THE UNDERGRADUATES OF SOUTHERN PUNJAB: http://doi.org/10.46536/jpumhs/2023/13.03.438 - Samina Waseem1, Anfal Hamza2, Muhammad Waqas3, Sana Tufail4, Hafiz Muhammad Rizwan5, Zulifqar Ali6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
Abstract ABSTRACT BACKGROUND: Tuberculosis TB, caused by Mycobacterium tuberculosis, is a significant health concern in Pakistan, ranking fifth globally with 510,000 new TB cases and approximately 15,000 drug-resistant TB cases emerging annually. Pakistan accounts for 61% of the TB burden in the WHO Eastern Mediterranean Region. There exists gap about knowledge of Tuberculosis, contributing to delayed diagnosis, alongside pervasive stigma. Knowledge about this disease among students of universities varies, underscoring the need for enhanced awareness in this population. OBJECTIVE: The objective of the study is to assess awareness of Tuberculosis among the undergraduates of Southern Punjab. METHODS: This Descriptive Cross Sectional study encompassed 1,384 students from six universities and seven medical colleges in South Punjab, employing convenient sampling methods. The data was collected through self-administered questionnaires covering personal, socioeconomic, knowledge-based, and perception-related aspects of Tuberculosis TB. Face-to-face interactions and an online Google Form questionnaire were used for data collection, subsequently analyzed using SPSS 2023. RESULTS: In this study of 1,384 undergraduate students in South Punjab, nearly half came from medical backgrounds, and the other half from non-medical disciplines. The majority fell within the 17-22 age range, and the gender distribution was almost equal. Remarkably, 96.34% of medical and 85.4% of non-medical students were familiar with tuberculosis TB. While symptoms like prolonged fever, weight loss, persistent cough, and chest pain were recognized, some misconceptions existed about fever and headache as TB symptoms. Roughly two-thirds of the students correctly understood that TB spreads through coughing and sneezing, while 19% believed it could spread through contact with objects. Preventive measures like covering the mouth and nose and avoiding spitting were noted. A significant portion believed that close contact with TB patients increased susceptibility, and a notable gender and study program influence was observed in various TB-related responses. Although there were some misconceptions, a majority believed TB to be treatable and preferred consulting a doctor if they suspected TB. TB stigma was moderate, with many students open to meeting TB-infected friends with precautions and perceiving some level of community support. CONCLUSION: This study highlights the awareness of Tuberculosis among South Punjab's undergraduate students. Despite misconceptions, many understand TB and its treatment. Stigma exists, but most students are open to meeting TB-infected friends with precautions. Gender and study program impact responses, suggesting the need for focused education.